U.S. Tax Reform : An Overview of the Current Debate and Policy Options - Dalsgaard, Thomas (IMF Working Papers; Working Paper ;, 2005)
In the context of the current tax policy debate in the United States, this paper reviews and discusses some of the main recurrent themes, as well as some of the most important tax reform proposals put forward over the past two decades. It finds that although there seems to be widespread agreement that the current tax system is too complex, unfair, and distortionary, little or no consensus exists on how best to improve it.